The Role of the Humbang Hasundutan District Health Service in Preventing and Controlling Stunting in Children Under Five - Lumayan Purba; Franklin Asido Rossevelt* (Universitas Syiah Kuala, 2024)
Stunting is one of the nutritional problems most often faced by young children. Stunting is a problem that must be addressed immediately because it can slow down a child's growth and development. In Humbang Hasundutan Regency, stunting is a prominent problem that requires serious efforts in prevention and management. Humbang Hasundutan District Health Service, as the agency authorized to prevent and control stunting. The research method used in this research is descriptive research with a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. Data obtained from the field was analyzed qualitatively using Jim Ife and Frank Tesoriero's theoretical approach which includes four indicators, namely facilitative role, educational role, representative role and technical role. The results of the research show that the Humbang Hasundutan District Health Service has implemented stunting prevention and management. Based on analysis carried out by the author using the theory of Jim Ife and Frank Tesoriero. That seen from the Facilitative role there are still obstacles so that the role is not yet optimal, the educational role is already running well, if seen from the representative role it is optimal however, in terms of regional government budget allocation it is not yet optimal and if seen from the technical role, the Health Service has implemented However, there are still obstacles in this role so that this role is not optimal.